Differences in mitral and tricuspid annular geometry in elite athletes with versus without functional mitral regurgitation: a 3D echocardiographic study. (14th October 2021) - Fabian, A; Lakatos, B K; Tokodi, M; Kiss, A; Sydo, N; Csulak, E; Babity, M; Szucs, A; Kiss, O; Merkely, B; Kovacs, A
Abstract:  : Intense exercise exposes the heart to significant hemodynamic demands, resulting in adaptive changes in cardiac morphology and function. Nevertheless, the athletic adaptation of the atrioventricular valves remains to be elucidated. Our study aimed to characterize the geometry of mitral (MA) and tricuspid (TA) annuli in elite athletes using 3D echocardiography. Thirty-four athletes presented with functional mitral regurgitation (FMR) were retrospectively identified and compared to 34 athletes without MR, and 34 healthy, sedentary volunteers. 3DE datasets were used to quantify MA and TA geometry and leaflet tenting by dedicated softwares. MA and TA areas, as well as tenting volumes, were higher in athletes compared to controls. MA area was significantly higher in athletes with MR compared to those without (8.2±1.0 vs. 7.2±1.0 cm 2 /m 2, p<0.05, Figure 1). Interestingly, athletes with MR also presented with a significantly higher TA area (7.2±1.1 vs. 6.5±1.1 cm 2 /m 2, p<0.05, Figure 2). Non-planar angle describing the MA's saddle shape was less obtuse in athletes without MR, whereas the values of athletes with MR were comparable to controls (Figure 1). The exercise-induced relative increases in left ventricular (35±25%) and left atrial (40±29%) volumes were similar; however, the increment in the MA area was disproportionately higher (63±23%, overall p<0.001). The relative increase in TA area (40±23%) was also higher compared to the increment in right ventricular volume (34±25%, p<0.05). Atrioventricular annuli undergo a disproportionate remodeling in response to regular exercise. Athletic adaptation is characterized by both annular enlargement and increased leaflet tenting of both valves. There are differences in MA geometry in athletes presented with versus without FMR. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Research, Development and Innovation Office of Hungary (NKFIA; NVKP_16-1-2016-0017 National Heart Program). The research was partly financed by the Thematic Excellence Programme (Tématerületi Kiválόsági Program, 2020-4.1.1.-TKP2020) of the Ministry for Innovation and Technology in Hungary, within the framework of the Therapeutic Development and Bioimaging programmes of the Semmelweis University.